Moral Competence of Teacher Education Students. The Role of Guided Reflection and Responsibility-Taking Opportunities - Tello, Daniel; Meza Pardo, Marisa; Retamal Salazar, Jaime (ETHICS IN PROGRESS, 2025)
Teacher education needs to focus on moral development and prepare their students to face the moral dilemmas in the teacher profession. The present study shows the first results of a long term research between 2017 and 2022 in 3 Chilean Universities. The relationship of learning environment, according to Responsibility Taking (RT) and Guided Reflection (GR) opportunities, on the differences on moral competence, was evaluated with a cross sectional design, comparing last with first year students (n=671). Results suggest a significant influence of RT and GR on moral competence. Being tutor at university is identified as one of those opportunities.